ANALISA DAMPAK PANDEMI COVID-19 TERHADAP PELUANG USAHA RUMAHAN MASYARAKAT KOTA DENPASAR - Dana Paramitha; Ayu Siska; Mila Rosa (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The island of Bali as a tourist area is very dependent on the stretching of domestic and foreign tourist visits. According to the latest data from the Central Statistics Agency, tourist visits have decreased drastically from the previous year. This decline certainly greatly affects the economic activity of small and medium-sized communities, quite a lot of them have to be temporarily laid off or laid off by the company where they work or even experience a decrease in sales turnover for those who come into contact with or contribute to tourism activities themselves. Denpasar City as the capital of Bali Province and the center of trade and tourist visits has experienced a significant impact due to the influence of the spread of the Covid-19 Virus. This affected economic condition will certainly create new problems if the community is ready to anticipate the economic condition of the tourism sector which has not yet recovered by exploring the economic potential that can cover the lack of people's income. Business fields that are developing in the field of culinary, traditional medicine, medical equipment and ornamental plants are the people's choice to survive. The use of information technology is also a must for the community to be applied so that they can continue to interact quickly to support the business activities being carried out. The COVID-19 pandemic situation has had a positive impact on the community to keep trying to continue the business that has been initiated as an alternative to additional family income in the future.